Analisis ketersediaan HOTS pada lembar kerja siswa kelas XI semester 1 - Syafrinaldi Syafrinaldi; Silvi Yulia Sari; Yenni Darvina; Wahyuni Satria Dewi (PILLAR OF PHYSICS EDUCATION, 2020)
In this 21st century, people are faced with an era of globalization that requires high thinking skills.  In line with the 2013 curriculum, teachers are required to carry out HOTS-based learning.  Factors that determine students can think at a high level are the teacher, students, learning models and teaching materials used.  One of the teaching materials used by teachers is student worksheets (LKS). The results of preliminary observations, it was found that the ability of HOTS students is still low based on the analysis of the results of the UAS grade XI semeseter 1 SMA in Padang.  In addition, the LKS used in West Sumatra is diverse and the availability of HOTS is unknown.  Therefore, research on the analysis of the availability of HOTS on Worksheets for Class XI Students Semester 1. The purpose of the study was to determine the availability of HOTS on the Physics Worksheets for Class XI High School Students Semester 1.This research is a descriptive study with a qualitative approach.  The population data in this study were all physics textbooks for class XI in semester 1 used by 23 schools in West Sumatra.  Sampling was done by purposive sampling technique. The data in this study were taken using LKS presentation analysis instruments and data collection techniques through documentation studies.Based on the research that has been done, it can be concluded that the analysis conducted on the availability of HOTS on the Physics Worksheet for Class XI High School Students Semester 1 related to the availability of HOTS components shows that the LKS who obtained the percentage of indicators on the highest HOTS component is the LKS SMA I 28.80%  in the HOTS Less Available category.  Whereas the Physics Worksheet that got the lowest percentage of indicators on the HOTS component, namely the 19.69% SMA IV LKS, was in the HOTS Unavailable category.